Current Model of public services in Europe and somes experiences for Vietnam - Trịnh Văn Tùng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The European Union's model of public services organization seems to be close to the model that Vietnam is pursuing because this model has the goal of creating a fairly balanced social security and welfare system to contribute to solving the limitations or disadvantages of the market economy. In particular, the model of public services provision of the European Union also shows the strong intervention role of the State when necessary. In the current period, facing the needs of theory and practice, the European Union is reforming or rather modernizing the public services delivery system. So, what factors led to the policy of modernizing or reforming the public services delivery system in the European Union? What are the characteristics, approaches and methods of reforming the public services delivery system in the European Union? What lessons can be drawn from the current process of reforming the public services delivery system in Vietnam? Answers to the above three questions constitute the core content of this paper.